1000 Strange But True Animal Facts (Parragon, 2014)
Discover the 1000 most extraordinary facts about animals ever! Which frog can break its own bones to make armour? What insect can survive being frozen solid? Which bird could life a human? These unbelievable creatures push every extreme of nature to the limit, and beyond. They're wild. They're out there. They're ready to be unleashed!